Kemenangan Romawi dalam Q.S. Al-Rūm [30]: 2–5 dan Refleksinya terhadap Kemerdekaan Indonesia: Kajian Historis dalam Tafsir Ibnu Katsir dan Safīnat Kallā Saya‘lamūn - Rafsanjani, Muhammad; Halimah, Ulfatul; Arrahmah, Faqru Nisa' (Tarikh : Journal of Islamic History and Civilization, 2025)
This study is motivated by the importance of interpreting Qur’anic verses through historical and contextual lenses to provide relevant meanings for the socio-political dynamics of Muslim communities across time. This article aims to explore the connection between the Roman victory mentioned in Q.S. Al-Rūm [30]: 2–5 and Indonesia’s independence struggle by analyzing Tafsīr Ibn Kathīr and Safīnat Kallā Saya‘lamūn. The study employs a qualitative method with a thematic tafsir approach and contextual-historical analysis. The findings reveal that the verses do not merely document the Persian-Roman conflict, but convey universal messages of hope, resistance, and the triumph of the oppressed. In the Indonesian context, the verses served as ideological and spiritual inspiration for Muslim freedom fighters resisting colonialism. The novelty of this research lies in its intertextual approach, linking Qur’anic texts, early Islamic history, and Indonesia’s national struggle—an area scarcely explored in classical or modern tafsir literature. The implications suggest the potential to strengthen Islamic narratives in shaping national historical consciousness and inform character education grounded in Qur’anic values.